“Análisis de Formación en las Organizaciones Políticas de Loja para la renovación de candidatos y su incidencia en la participación en las elecciones seccionales y anticipadas 2023” - Diaz Veintimilla, Anabell del Cisne (2024)
The analysis of political training in Loja's political organizations for the renewal of candidates highlights the importance of preparing new political cadres. The general objective of this study was to analyze the relationship between the political training offered by Loja's organizations and the renewal of their candidates for the 2023 elections. It was used a mixed methodology by combining quantitative and qualitative approaches. This included the participation of experts in political analysis, leaders of organizations and young candidates who participated in the 2023 elections. Likewise, surveys and an observation matrix to various political organization were realized, in order to know the perception of youth participation in politics. The results reveal that political training in Loja is insufficient to prepare new candidates, since there are no training schools, forcing candidates to prepare on their own. Youth participation is limited due to the lack of training opportunities and political support. Finally, it is concluded that according to the Code of Democracy, political organizations must guarantee a 25% inclusion of young people in the lists for popular elections. Likewise, article 331 requires parties to maintain political training centers to train their candidates, which highlights the importance of strengthening these programs for greater inclusion and renewal of leaders in local politics. Keywords: Political training, candidate renewal, youth participation, new cadres, political organizations.